Implementation of Lesson Study as a Strategy to Optimize Differentiated Instruction in English Language Teaching - Rahmawati Upa; Sri Damayanti; Hafirah Patang; Paldy; Miltan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aims at investigating how lesson study can be effectively utilized to support differentiated instruction in English language classrooms. This research used a qualitative approach with a case study design to gain an in-depth understanding of how lesson study can support differentiated instruction in English language classrooms. The subjects were 12 English teachers, 4 English lecturers and students participating in the lesson study process. This research used purposive sampling technique in selecting participants based on specific criteria, such as teachers, lecturers, and students experienced in differentiated instruction and engage in the lesson study process. It was conducted in SMK Negeri 1 Palopo with two cycles. The research procedure consisting of four: planning, implementation, observation, and reflection. Over two cycles, the implementation of different process differentiation techniques revealed valuable insights. In the first cycle, the use of process differentiation through media choice allowed students autonomy in their learning but highlighted the challenges faced by lower-ability students. Heterogeneous grouping led to passive participation among weaker students, as they relied on their higher-ability peers, and the freedom to choose media did not fully address their learning needs. In the second cycle, process differentiation was enhanced by introducing homogeneous groups and worksheets tailored to students' abilities, alongside increased teacher assistance for the basic group. This more structured approach resulted in significant improvements in student engagement, particularly among lower-ability students who benefitted from focused support. The advanced and intermediate groups also thrived with tasks matched to their skill levels, demonstrating the success of ability-based differentiation.